Entrainment performance enhancement of HVAC systems with active chilled beams - Guan, Zheming (2017)
Heating, ventilation and air conditioning (HVAC) systems with active chilled beams (ACB) terminal units are attracting increasing attention in both theoretical research and practical application, due to their superior benefits compared with variable air volume (VAV) systems. In conventional VAV systems, a large volume of recirculation air is distributed through ductwork by big exhaust and supply fans. The energy consumed by these fans is enormous. As water has a much higher heat capacity compared with air, the ACB system utilizes water instead as the media of heat exchange, saving energy from delivering less volume of air. The volume of water transferring the same cooling is much smaller than air. Therefore, ACB systems are more energy efficient, by taking advantage of using less energy in distributing the chilled water directly to the air-conditioned space. Besides the energy saving benefits, ACB system can save the space above suspended ceilings. As most of the space is occupied by air supplying duct, the bottleneck for buildings with VAV system diminishing the space is to decrease the size of duct. As the ACB system requires less air supplying, it is an inherent character of ACB system to occupy less space above the ceiling, so that the floor-to floor height of a building can be decreased. Our research is dedicated how to enhance the energy efficiency performance of HVAC systems with space-friendly ACB terminal units. To achieve this, we make use of different tools to investigate the energy efficiency of ACB systems in many aspects, especially by confining the geometric factors of terminal unit. The energy efficiency of the whole system can thus be increased. In the meanwhile, we also suggest reduction of the height of terminal unit, so that the ACB system can show a greater advantage in term of space saving. By these means, the economic value of the ACB system, as well as the user acceptance can be increased.